Estrategias de publicidad en el hotel oasis de la ciudad de Babahoyo en el segundo semestre, 2022 - Santillán Mayorga, Leidy Nathaly (2023)
The general objective of this study was to analyze the advertising strategies at the Oasis Hotel in the city of Babahoyo during the second half of 2022. The results revealed that the hotel faces a lack of recognition and visibility in the local tourism market, which has led to low room occupancy and limited revenue generation. In addition, the need to improve the decoration and furniture of the rooms was identified to meet customer expectations. The hotel's current advertising strategies focus on Facebook and Instagram, with Twitter and LinkedIn being considered in the future. Indicators of success for these strategies include increase in followers, customer engagement, and increase in website traffic. However, it was found that the majority of people surveyed were not aware of these strategies, highlighting the importance of improving online visibility and communication. The hotel's evaluation showed positive aspects, such as a welcoming and efficient reception, clean and well-maintained common areas, and friendly and helpful staff. However, areas for improvement were identified in the decoration and furnishing of the rooms, as well as the maintenance of the outdoor areas. In conclusion, this study highlights the critical importance of addressing the lack of effective advertising and promotion strategies at the Babahoyo Oasis Hotel, improving market visibility, optimizing online communication, and addressing areas of improvement identified in the hotel assessment are key steps to increasing room occupancy, revenue, and guest satisfaction, which would benefit both the hotel and its customers. the local economy.